Biological control of Subterranean termite, Coptotermes curvignathus (Isoptera: Rhinotermitidae) using indigenous bacteria from its gut and foraging pathway - Wong, Wan Zhen (2016)
The subterranean termite, Coptotermes curvignathus, is one of the most prominent plantation pests that feed exclusively from lignocellulose diets. The lignocellulose digestion of termite is made possible by host-secreted enzymes, specialized gut physiology and microbial gut symbionts. Since termites are very dependant on these microbes to digest the food for survival, termite can be controlled by disturbing the micro-ecology of termite gut by using its own bacteria. Through this study, screening and identification of culturable aerobic bacteria among communities from the gut and foraging pathway of C. curvignathus was carried out. Since these bacteria can also lead to pathological states upon reaching favourable conditions, the susceptibility of C. curvignathus was evaluated for opportunistic pathogen using culturable aerobic bacteria isolated from termite gut and its foraging pathways. A total of 24 bacteria species have been identified mainly from the family Enterobacteriaceae by using Biolog Gen III. Overall, the bacteria species in the termite gut differ from those of foraging pathway within same location except for Acinetobacter baumannii which was the only bacteria species found in both habitats. Coptotermes curvignathus was found to be susceptible to both Microbacterium sp. and Serratia marcescens in varied concentrations by using ingestion and physical contact method under laboratory conditions. Serratia marcescens showed the highest mortality of 66.4% and 59.2% at concentrations of 109 CFU/mL and 106 CFU/mL in ingestion method and was closely followed by Microbacterium sp. (65.2%) at concentrations of 109 CFU/mL. While on median lethal study, Pseudomonas aeruginosa had the effective LC50 (107 CFU/mL) and LT50 at concentration 1012 CFU/mL (5 days) under laboratory conditions. Serratia marcescens and P. aeruginosa was applied onto soil, filter paper and wood. It can be concluded that S. marcescens with filter paper application method gave the highest termite mortality (100% in 1012 CFU/mL). Furthermore, the ability for bacteria to self-sustain on wood and filter paper is low. Serratia marcescens is a chitin degrading bacteria. Nutrient (chitin) was treated on filter paper to allow the growth of S. marcescens. From observation, S.marcescens survived longer in chitin-treated filter paper. The termite was forage on chitin-treated filter paper with S. marcescens. These results are a valuable tool for the biocontrol of termite. Conclusively, subterranean termite, C. curvignathus can be controlled by using indigenous bacteria from its gut and foraging pathway.